ANALISIS USAHA DAN STRATEGI PENGEMBANGAN PEMASARAN BOLU KEMOJO DI KELURAHAN TANGKERANG SELATAN KECAMATAN BUKIT RAYA KOTA PEKANBARU (STUDI KASUS PADA USAHA CIK PUAN) - Imelda Putryansyah; Darus (UIR Press, 2021)
This study aims to analyze the characteristics of the entrepreneur and the business profile of the kemojo sponge, the procurement of raw materials and supporting materials, processing technology, costs, income, business efficiency and added value, and strategy for marketing development of the kemojo sponge marketing. The method used was the survey method. Respondents were collected 1 manager and 2 workers in Tangkerang Selatan Village, Bukit Raya District, Pekanbaru City. The data collected consistsed of primary data and secondary data and were analyzed using descriptive qualitative and quantitative. The results showed that the age of manager was 49 years, while the average age of the workers was 23 years old. The length of education of manager was 12 years, while the worker was 12 years on avera. The family member of the manager was 3 people with 13 years experience, while the worker has an average experience of 4.5 years. The business has been starting from 2007 and had a business license. The source of capital from the Bank loan with household scale and used worker as 2 people. The use of raw materials per process production was 5 kg of flour, Rp. 198,575 of supporting materials with the simple technology. The total cost was Rp. 319,020, the gross income was Rp. 1,020,000 and net income of IDR 700,980 per production process on average. The added value obtained was IDR 149,500/kg with the RCR of 2.20. Based on the strategy of developing the kemojo sponge agro-industrial business, it is stated that this business is in quadrant I, so it can perform the SO strategy, including maintaining product quality to increase consumer satisfaction and maintaining affordable product prices by looking at market information.